Produtos em homologia e cohomologia na categoria dos complexos simpliciais - Bugs, Cristhian Augusto (Universidade Federal de São Carlos, 2004)
In this work we present fundamental theory to establish the coordinates of the Kronecker Index, Cup and Cap Products in the finite Simplicial Complexes category in terms of chain and cochain.
Keywords: Topologia algébrica; Homologia simplicial; Produto cup; Produto cap; CIENCIAS EXATAS E DA TERRA::MATEMATICA